Dermanyssus gallinae eradication approach – application of inert compounds and integral animal health protection - Aleksandar Pavlićević; Radomir Ratajac; Danijela Horvatek Tomić; Igor Stojanov; Igor Pavlović (Archives of Veterinary Medicine, 2018)
The generally accepted approach to D. gallinae control is based on the control of infestations. The reduction of D. gallinae infection to an acceptable level can temporarily prevent its harmful effects on the health status ofpoultry. However, the reduced number of D. gallinae continues to persist in poultry environment resulting in an intensive increase of infestation rate and consequent transmission of infectious and contagious diseases. Contrary to suppression, the eradication approach completely eliminates D. gallinae thus improving general health status of the flock and providing the control of infectious and contagious diseases associated with this organismand eliminating other adverse effects. Biological efficiency and selection of inert compounds was performed in laboratory conditions. The previous experience with application of SiO2 formulations in practice confirmed thepossibility of successful eradication in 8 cases (combined application of liquid and powdered form). New generation of inert compounds (P 547/17)  showed a range of superior properties as compared with SiO2 formulations,especially in view of high and long-lasting residual effects on non-absorbent surfaces. In laboratory conditions, after 7 months, the layer formed by a 20% working emulsion on a metal substrate exhibited efficiency of 92%after 1-hour exposure. In clinical conditions, the presence of mites was not detected even after 6.5 months of the settlement of the flock. Clinical tests of inert oils are still ongoing, but their high potential for the eradication of D.gallinae The eradication of D. gallinae is highly complex procedure, which cannot be performed at all times and in all conditions. The conditions for the eradication of D. gallinae using inert compounds include adequate hygienic preparation of the facilities while still empty, adequate application of selected compounds, and then adequate ambient temperatures which leads to increase of mites activity. The program of D. gallinae control includesprocedures for the preparation, implementation, eradication checks, and prevention of re-infestation